Transcriptional regulation of the gonadotropin-releasing hormone receptor (GnRHR) gene by glucocorticoids - Fernandes, S. M. (Sandra Maria) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2007.